Goals of care discussions in acute hospital admissions – Qualitative description of perspectives from patients, family and their doctors. Issue 12 (December 2021) - Harris, Elly; Eng, Derek; Ang, QiKai; Clarke, Emily; Sinha, Atul
Highlights: GOC discussions are life-saving procedure focused, not patient values based. Patients and family are often unprepared for GOC discussions. Previous end-of-life care experiences influence GOC decision-making. Family presence in GOC discussions is important and desired. Abstract: Objective: Goals of care discussions guide care for hospital inpatients at risk of deterioration. We aimed to explore patient and family experience of goals of care during the first 72 h of admission along with their doctor's perspective. Methods: A qualitative descriptive study. Patients, family and doctors who participated in a goals of care discussion during an acute hospital admission at an Australian tertiary teaching hospital were interviewed in 2019. Results: Many participants found goals of care discussions appropriate and reported understanding. However, communication was commonly procedure-focused, with questioning about preferences for cardiopulmonary resuscitation and intubation. Some considered the discussion as inapplicable to their state of health, and occasionally surprising. Participants commonly related goals of care with death, and without context, this led to fear of abandonment. Previous experience with end of life care influenced decision-making. Preference for family presence was clear. Conclusions: This study identifies deficiencies in goals of care communication in the acute hospital setting. Discussions are life-saving-procedure focused, leading to poor understanding and potentially distress, and jeopardising patient-centred care. Practice implications: Assessment of patient values and clear communication on the aims of goals of care discussions is essential to optimise patient and institutional outcomes. Clinicians should consider environment and invite family participation.